(untitled) (Swiss Medical Weekly, 2017)
Because of the worldwide aging of populations, Alzheimer’s disease and other dementias constitute a devastating experience for patients and families as well as a major social and economic burden for both healthcare systems and society. Multiple potentially modifiable cardiovascular and lifestyle risk factors have been associated with this disease. Thus, modifying these risk factors and identifying protective factors represent important strategies to prevent and delay disease onset and to decrease the social burden. Based on the cognitive reserve hypothesis, evidence from epidemiological studies shows that low education and cognitive inactivity constitute major risk factors for dementia. This indicates that a cognitively active lifestyle may protect against cognitive decline or delay the onset of dementia. We describe a newly developed preventive programme, based on this evidence, to stimulate and increase cognitive activity in older adults at risk for cognitive decline. This programme, called “BrainCoach”, includes the technique of “motivational interviewing” to foster behaviour change. If the planned feasibility study is successful, we propose to add BrainCoach as a module to the already existing “Health Coaching” programme, a Swiss preventive programme to address multiple risk factors in primary care.